Strategie di internazionalizzazione e grande distribuzione nel settore dell'abbigliamento - Ciappei, Cristiano (Firenze University Press, 2006)
The Stanze della Moda project has set up an Observatory with the purpose of economic and management monitoring of the fabric of the Florentine companies through a marketing and research workshop. The analysis of several major international retailers demonstrates the emergence of a successful business model which, albeit in some respects idiosyncratic and difficult to transfer, represents an innovative stimulus for companies in the sector that want to redefine their competitiveness in the face of the altered market conditions. The focus on the Florentine companies delineates the ways in which the local manufacturers intercept the purchasing channels of major retail, creating a mediated form of sales on the international markets.